KAJIAN KEBUTUHAN DIKLAT PENYELAMATAN DIRI PADA KONDISI DARURAT DI BANGUNAN TINGGI MENGGUNAKAN TEKNIK ASCENDINGDAN DESCENDING - Yudiana Hadiyat; Leni Nurliana (PPSDM Geominerba, 2020)
It has often happened that victims have fallen or been trapped in tall buildings that are on fire, due to the delay in the evacuation or rescue process by the existing external rescue team due to access to the fire location that is not smooth due to traffic jams or indeed limited access, such as narrow roads or unavailability of rescue facilities. fire emergency on site, or insufficient available facilities. The weaknesses of the current emergency rescue system need to be anticipated by providing alternative independent rescue methods that can be carried out by the building occupants themselves. This scientific study aims to determine whether the training for survival in emergency conditions in tall buildings using ascending and descending techniques is needed by residents of tall buildings, the research method used is descriptive qualitative method, from the research it was found that the training for this method of self-rescue is very important, needed and can be given in the form of short 2–3 days training or 1 day technical guidance repeatedly.